2013
DOI: 10.1128/cmr.00059-12
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Virulence: a Successful or Deleterious Association in the Bacterial World?

Abstract: SUMMARY Hosts and bacteria have coevolved over millions of years, during which pathogenic bacteria have modified their virulence mechanisms to adapt to host defense systems. Although the spread of pathogens has been hindered by the discovery and widespread use of antimicrobial agents, antimicrobial resistance has increased globally. The emergence of resistant bacteria has accelerated in recent years, mainly as a result of increased selective pressure. However, although antimicrobial resistance and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
630
6
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 833 publications
(713 citation statements)
references
References 461 publications
(480 reference statements)
23
630
6
14
Order By: Relevance
“…El uso muy difundido, y muchas veces inapropiado, de los antibióticos en muchas partes del mundo (tanto en medicina humana como veterinaria) ha llevado a que ocurra el fenómeno de "presión selectiva" sobre las bacterias, es decir, las cepas que adquieren resistencia sobreviven y se reproducen, incrementándose así el porcentaje de microorganismos resistentes (1,2).…”
unclassified
“…El uso muy difundido, y muchas veces inapropiado, de los antibióticos en muchas partes del mundo (tanto en medicina humana como veterinaria) ha llevado a que ocurra el fenómeno de "presión selectiva" sobre las bacterias, es decir, las cepas que adquieren resistencia sobreviven y se reproducen, incrementándose así el porcentaje de microorganismos resistentes (1,2).…”
unclassified
“…Se han reportado seis grupos principales en la CTX-M: bla CTX-M-1 , bla CTX-M-2 , bla CTX-M-8 , bla CT-XM-9 , bla CTX-M-25 y bla CTX-M-45 ; bla CTX-M-15 ha sido el de mayor diseminación, con un comportamiento pandémico. En los últimos años, se ha reportado en Argentina, Bolivia, Colombia, Perú y Venezuela (24-29) la presencia de otras variantes: bla CTX-M-2 , bla CTX-M-8 y bla CTX-M-9 (variente bla CTX-M-65 ), además de la asociación con bla SHV y bla TEM , y la resistencia simultánea a otros grupos de antimicrobianos en aislamientos provenientes de hospitales y de la comunidad (8)(9)30). Dichos hallazgos coinciden con los de la presente investigación, en la cual se evidenció un predominio de aislamientos productores de bla CTX-M-8 , bla CTX-M-2 y bla CTX-M-15 , a pesar del número reducido de cepas no relacionadas a nivel clonal que se analizaron.…”
Section: Discussionunclassified
“…Por el contrario, Johnson,et al (21), determinaron la existencia de una relación inversamente proporcional entre el número de factores de virulencia y la presencia de genes de resistencia en cepas de E. coli de filogrupos diferentes. Es probable que la coexistencia de factores determinantes de virulencia y de mecanismos de resistencia en cepas de E. coli sea el resultado de un proceso de evolución gradual concertada; además, la asociación de estas características depende del nicho ecológico, la presión selectiva del ambiente, las características bacterianas en diferentes regiones geográficas y de la reacción del sistema inmunitario del huésped sensible (2,8,44).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Whereas the exposed isolate showed changing the sensitivity for (MEC) to resistance in the last 3 passages, resistant bacteria generations was associated in most cases, either directly or indirectly with decreased virulence and fitness, genetic events also associated with the evolution of pathogen on virulence and fitness costs, in gramnegative, β-lactamases production was the most prevalent mechanism of β-lactam resistance, followed by permeability alterations, with extrusion by efflux pumps, and lesser extent penicillin binding protein (PBP) alterations as (Alejandro et al, 2013) reported, thus we suggested that the plotted of pathogenic K. pneumoniae to laser may make cell wall/cell membrane alteration. Whereas the gradual changing from resist of (SAM) to sensitive in 3rd, 4th and 5th, and 6th (Table 5).…”
Section: Finally Selection By Using Low Power Laser Lightmentioning
confidence: 99%